Inland and saltmarsh feeding of wintering Brent Geese in Essex - White-Robinson, Richard (Wildfowl, 1982)
Brent Geese Branta bernicla bernicla wintering in Essex during 1978/79 were studied on saltmarsh and farmland. The majority of the birds spent 87% of their day feeding inland, making trips to saltmarsh only when disturbed. Saltmarsh feeding was most common around high tide, and the density of birds supported on inland pasture was three times that on saltmarsh. Disturbance levels were similar in the two habitats. Estimation of goose energy budgets emphasizes the combined roles of disturbance-free refuges and scaring over crops for managing geese.